The Static and Dynamic Mechanical Properties of Magnetorheological Silly Putty - Fei Guo; Cheng-bin Du; Guo-jun Yu; Run-pu Li (Advances in Materials Science and Engineering)
A novel magnetorheological material defined as magnetorheological Silly Putty (MRSP) is prepared by dispersing soft magnetic particles into Silly Putty matrix with shear stiffening property. Static mechanical properties including creep and stress relaxation and dynamic rheological properties of MRSPs are tested by rheometer. The experimental results indicate that the external magnetic field exerts significant influence on the creep and relaxation behaviors. Moreover, the storage modulus of MRSPs increases sharply in response to the external stimuli of increasing angular frequency automatically and can be enhanced by external magnetic field. Besides, temperature plays a key role in shear stiffening and magnetorheological effect of MRSPs. Furthermore, considering the obstruction to the particle chains formation induced by Silly Putty matrix, a nonperforative particle aggregated chains model is proposed. The model curve is in consistency with experimental data, which means it can describe magnetoinduced behavior of MRSPs well.